Turn-turn short circuit fault management in permanent magnet machines - Arumugam, Puvaneswaran; Hamiti, Tahar; Gerada, C. (Institution of Engineering and Technology, 2015)
This paper presents a systematic study on turn-turn short circuit fault and ways to manage them to provide a basis for comparison of the various options available. The possible methods to reduce the likelihood of the winding SC fault and the fault mitigation techniques related to such faults are discussed. A Finite Element (FE) analysis of a surface-mount Permanent Magnet (PM) machine under application of different mitigation techniques during a turn-turn fault is presented. Both machine and drive structural adaptations for different fault mitigation techniques are addressed. Amongst the investigated fault mitigation techniques, the most promising solution is identified and validated experimentally. It is shown that the shorting terminal method adopting vertical winding arrangement is an effective method in terms of the implementation, reliability and weight.